Drying of Mint and Basil Leaves for The Herbal Blended Beverage Development - Khiewnavawonsga, Sorraya; Poonlarp, Pichaya; Hao, Nguyen Nhu (Food and Applied Bioscience Journal, 2018)
The objective of this study was to develop the herbal blended beverage made with 4 herbs: mint leaves, basil leaves, fennel seed and licorice root. Tray drying method was used for drying mint leaves and basil leaves at two different temperatures: 50ºC and 55ºC. Product quality was determined by measuring antioxidant activity by DPPH free radical method and total phenolic compound method. Drying kinetic, color and water activity were also analyzed. Results showed that drying mint leaves and basil leaves at 55ºC was better than drying at 50ºC. Sensory analysis was conducted to find appropriate proportion of ingredients. Herbal blended beverage with 40% of dried mint, 10% of dried basil, 30% of dried licorice root, and 20% of fennel seed was most accepted for all sensory attribute: appearance, color, odor, flavor, after taste, and overall.